English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

steps

2007-01-21 09:25:14 · 1 answers · asked by brian g 2 in Science & Mathematics Mathematics

1 answers

If you're just FOILing it, treat it like you would a normal variable expression:

(6+5rad3)(1-rad3) = (6)(1) - (6)(rad3) + (5rad3)(1) - (5rad3)(rad3)
= 6 - 6rad3 + 5rad3 - 5(3)
= 6 - rad3 - 15
= -9 - rad3

2007-01-21 14:06:09 · answer #1 · answered by igorotboy 7 · 0 0

fedest.com, questions and answers